Nurse’s daily life facing the patient in palliative care in terminality in wards (Research, Society and Development, 2021)
Objective: To understand the daily routine of nurses in terms of patient care in palliative care at the end of life in wards. For this, facilitating and limiting points were analyzed, as well as proposals to optimize care in the finiteness of life. Methodology: Qualitative, descriptive and exploratory research, carried out with 14 nurses from open inpatient units at a university hospital in the city of Rio de Janeiro between August and November 2020. For data collection, after approval by the Research Ethics Committee, a semi-structured interview was used and, in the data treatment, Laurence Bardin’s content analysis was used. Results: Three categories emerged in the analysis: “Facilitating factors for the assistance of nurses in palliative care in the terminal”, “Limiting factors for the assistance of nurses in palliative care in the terminal” and “Nurses’ proposals to improve the assistance in palliative care in the terminal”. The difficulties presented were lack of continuing education, teamwork, routines and difficulty in dealing with death, in addition to the epidemic caused by covid-19. Proposals for training and emotional support for the team and creation of a specific sector were suggested. Conclusion: The reports identify an environment that does not encourage the exercise of autonomy. As limitations, the need for studies in the area from the Brazilian perspective are highlighted – from its implementation in the country to pressing research problems – and the necessary visibility for those concerned from a biopolitical perspective.